DEPENDENT CLAUSES FROM THE PERSPECTIVE OF AN INTEGRATED APPROACH - Мирјана Н. Којић (Faculty of Philosophy, University of Novi Sad, City Library of Pančevo, 2013)
This paper analyses subordinate clauses from the perspective of an integrated approach, by making a parallel with the traditional analysis of the communicative sentence as well as the subordinate clause itself within several syntactic units. The analysis of dependent clauses has been carried out on the basis of the responses of the Philological High School students. The statistics review is an illustration of the level of knowledge and students' achievement within this area.